KAMUS BAHASA BIAK BERBASIS ANDROID: ANDROID BASED BIAK LANGUAGE DICTIONARY - Novelia Leatemia; Julius Panda Putra Naibaho; Cristian Dwi Suhendra (Universitas Papua, 2022)
The Biak Language Dictionary application is made using designs and blocks through open source IDE tools, namely kodular and uses the Phpmyadmin MySQL Database as a dictionary database storage area. This Biak Language Dictionary application is designed with a dictionary working system in general, namely an application that contains a list of vocabulary of a language that is arranged alphabetically in this case the Biak language, has an Input function and an Output function. This dictionary application can be helpful and useful for the local Biak community or other general public in communicating using the Biak language, as well as helping to preserve regional culture through regional languages, especially the Biak language, which until now still lacks knowledge about the Biak language.